MIMO Technology is Used to Improve the Security Capacity Stability of Rayleigh Wiretap Channel - Xie, Junxi (International Journal of Computer Science and Information Technology, 2024)
This paper analyzes the security capacity when the Rayleigh channel codec is known, and studies the relationship between the transmit power, the estimation error and the security capacity difference. The results show that the increase of transmit power can make the security capacity difference tend to a stable value, which indicates that the influence of imperfect channel state information on the security capacity tends to be stable. By comparing the transmission power of SISO system and MIMO system, it is proved that MIMO system usually has higher transmission power under the same received power, so it is more suitable for improving the security capacity stability of Rayleigh channel.